Skin manifestations in acute arsenic poisoning from the Wakayama curry-poisoning incident - Uede, K.; Furukawa, F. (British journal of dermatology (1951), 2003)
Summary Background  Four people died and 63 others became ill after eating arsenic‐laced curry served at a community festival in Wakayama, Japan, on 25 July 1998. Although dermatological manifestations after the acute ingestion of arsenic have seldom been documented, they were observed in 56% of the victims in the Wakayama curry‐poisoning incident. Objectives  To characterize the skin manifestations due to acute arsenic poisoning. Methods  Four of the 67 patients with arsenic poisoning died, and the remaining 63 patients served as subjects for this study. The dermatological findings were extracted from the medical charts at the institutions which admitted the victims, and from the results of a medical inquiry and examinations during a health screening 3 months after the incident. Results  Dermatological findings were observed in 56% of the victims during the acute stage of poisoning. Facial oedema was observed in 13 patients, transient flushing erythema in five, conjunctival haemorrhage in 15, maculopapular eruptions in the intertriginous areas in eight, acral desquamation in 11, and herpesvirus infection in three. The histopathological findings of the maculopapular eruptions showed moderate to marked perivascular infiltration with endothelial swelling. Examination of 21 patients at 3 months after their exposure to arsenic revealed ungual changes including Mee's or Beau's lines in 17 cases, periungual pigmentation in nine, and acral desquamation in four cases. Conclusions  Our observations indicate that skin lesions are common in patients with acute arsenic poisoning; these findings may provide information of diagnostic significance.